Left Ventricular Dimensions and Diastolic Function Are Different in Throwers, Endurance Athletes, and Sprinters From the World Masters Athletics Championships - Hoffmann, Fabian; Moestl, Stefan; Wooten, Savannah V.; Stray-Gundersen, Sten; Tomczak, Corey R.; Tank, Jens; Tanaka, Hirofumi; Rittweger, Jörn; Chilibeck, Philip D. (Frontiers in Physiology, 2021)
There is controversy whether a lifetime of heavy resistance training, providing pressure-overload, is harmful for left ventricular function. We compared left ventricular dimensions and function in elite Masters athletes involved in throwing events (requiring strength; n = 21, seven females, 60 ± 14 years) to those involved in endurance events (n = 65, 25 females, 59 ± 10 years) and sprinting (n = 68, 21 females, 57 ± 13 years) at the 2018 World Masters Athletic Championships. Left ventricular dimensions and function were assessed with B-mode ultrasound and Doppler. The ratio of left ventricular early diastolic peak filling velocity to peak velocity during atrial contraction (E/A) across the mitral valve and the ratio of E to velocity of the E-wave (E’) across the lateral and septal mitral annulus (E/E’) were used as indexes of left ventricular diastolic function. Intra-ventricular septal wall thickness was greater in throwers compared to sprinters (11.9 ± 2.2 vs. 10.3 ± 2.3 mm; p = 0.01). Left ventricular end diastolic diameter/body surface area was higher in endurance athletes and sprinters vs. throwers (25.2 ± 3.0, 24.3 ± 3.1, and 22.0 ± 3.1 mm/m2, respectively, p < 0.01). The E/A was higher in endurance athletes and sprinters vs. throwers (1.35 ± 0.40, 1.37 ± 0.43, and 1.05 ± 0.41, respectively; p < 0.01). The E/E’ was lower in endurance athletes and sprinters vs. throwers (6.9 ± 1.8, 6.6 ± 1.9, and 8.1 ± 1.9, respectively, p < 0.05). Compared to age-matched historical controls (n > 1,000; E/A = 1.06; E/E’ = 7.5), left ventricular diastolic function was not different in throwers, but superior in endurance athletes and sprinters (p < 0.01). Masters throwers have altered left ventricular dimensions and function vs. other athletes, but a lifetime of heavy resistance training does not appear to alter left ventricular function compared to age-matched controls.